Angiotensin 1-7 protects against Angiotensin II-Induced Endoplasmic Reticulum Stress and Endothelial Dysfunction via Mas Receptor - Murugan, Dharmani Devi; Lau, Yeh Siang; Lau, Wai Chi; Mustafa, Mohd Rais; Huang, Yu (Public Library of Science, 2015)
Angiotensin 1-7 (Ang 1-7) counter-regulates the cardiovascular actions of angiotensin II (Ang II). The present study investigated the protective effect of Ang 1-7 against Ang II-induced endoplasmic reticulum (ER) stress and endothelial dysfunction. Ex vivo treatment with Ang II (0.5 mu M, 24 hours) impaired endothelium-dependent relaxation in mouse aortas; this harmful effect of Ang II was reversed by co-treatment with ER stress inhibitors, l4-phenylbutyric acid (PBA) and tauroursodeoxycholic acid (TUDCA) as well as Ang 1-7. The Mas receptor antagonist, A779, antagonized the effect of Ang 1-7. The elevated mRNA expression of CHOP, Grp78 and ATF4 or protein expression of p-eIF2 alpha and ATF6 (ER stress markers) in Ang II-treated human umbilical vein endothelial cells (HUVECs) and mouse aortas were blunted by co-treatment with Ang 1-7 and the latter effect was reversed by A779. Furthermore, Ang II-induced reduction in both eNOS phosphorylation and NO production was inhibited by Ang 1-7. In addition, Ang 1-7 decreased the levels of ER stress markers and augmented NO production in HUVECs treated with ER stress inducer, tunicamycin. The present study provides new evidence for functional antagonism between the two arms of the renin-angiotensin system in endothelial cells by demonstrating that Ang 1-7 ameliorates Ang II-stimulated ER stress to raise NO bioavailability, and subsequently preserves endothelial function.